Dissertation presentation in part consideration for MSc. in Supply Chain and Operations Management - Olufeko, Olajumoke T. (2011)
Foreign direct investment (FDI) is what most countries strive to attract as it is an advantageous tool for economic development. Nigeria not being left out also joined the rest of the world in seeking FDI as shown by the formation of the New Partnership for Africa’s Development(NEPAD, which is responsible for attracting FDI to Africa as a major component. This study looks into the impact of foreign direct investment on Nigerian economy between 1991 and 2010.